1999
DOI: 10.1073/pnas.96.6.3314
|View full text |Cite|
|
Sign up to set email alerts
|

Spatial attention affects brain activity in human primary visual cortex

Abstract: Biochemistry. In the article "Clonal selection and in vivo quantitation of protein interactions with protein-fragment complementation assays" by Ingrid Remy and Stephen W. Michnick, which appeared in number 10, May 11, 1999, of Proc. Natl. Acad. Sci. USA (96, 5394-5399) Immunology. In the article entitled "Murine natural killer cells contribute to the granulomatous reaction caused by mycobacterial cell walls" by I. Apostolou, Y. Takahama, C. Belmant, T. Kawano, M. Huerre, G. Marchal, J. Cui, M. Taniguchi, H. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

47
385
10
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 592 publications
(449 citation statements)
references
References 49 publications
47
385
10
3
Order By: Relevance
“…BOLD fMRI in such cases will reveal significant activation and will appear to provide results that do not match those of neurophysiology. In this manner a number of experiments in monkeys appear to be inconsistent with fMRI experiments employing the same tasks or stimulation conditions (Tong et al 1998;Gandhi et al 1999;Polonsky et al 2000;Kastner & Ungerleider 2000) (see also review by Blake & Logothetis (2002)), as the synaptic activity produced by lateral or feedback input is visible with imaging but not always with single-unit recordings. A good example is the measurement of the effects of spatial attention on neural activation.…”
Section: The Neural Origin Of Bold Responsementioning
confidence: 99%
See 1 more Smart Citation
“…BOLD fMRI in such cases will reveal significant activation and will appear to provide results that do not match those of neurophysiology. In this manner a number of experiments in monkeys appear to be inconsistent with fMRI experiments employing the same tasks or stimulation conditions (Tong et al 1998;Gandhi et al 1999;Polonsky et al 2000;Kastner & Ungerleider 2000) (see also review by Blake & Logothetis (2002)), as the synaptic activity produced by lateral or feedback input is visible with imaging but not always with single-unit recordings. A good example is the measurement of the effects of spatial attention on neural activation.…”
Section: The Neural Origin Of Bold Responsementioning
confidence: 99%
“…Attentional effects on the neurons of striate cortex have indeed been very difficult to measure in monkey electrophysiology experiments (Luck et al 1997;McAdams & Maunsell 1999). However, for similar tasks strong attentional effects have been readily measurable with fMRI in human V1 (Tong et al 1998;Gandhi et al 1999;Kastner & Ungerleider 2000). In addition, attentional effects in area V4 were found to be considerably larger in human fMRI than monkey electrophysiology (Kastner et al 1998;Ress et al 2000).…”
Section: The Neural Origin Of Bold Responsementioning
confidence: 99%
“…LFPs are a prime candidate for correspondence with BOLD signals because synaptic activity constitutes the bulk of neuronal metabolism (Sibson et al 1998), and BOLD responses have been observed in the absence of measurable single-unit activity (Gandhi et al 1999;Blake and Logothetis 2002;Polonsky et al 2000). Nonetheless, the correlation between BOLD signals and MUA was consistently significant although weaker than that with LFP (e.g., Logothetis et al 2001).…”
Section: Introductionmentioning
confidence: 98%
“…For one, attending a location boosts the neural activity to elements presented at that location (Brefczynski & DeYoe, 1999;Datta & DeYoe, 2009;Gandhi, Heeger, & Boynton, 1999;Somers, Dale, Seiffert, & Tootell, 1999). It has further been suggested that attending both rival images leads to a boost in the neural response, which increases the effective contrast of rivaling images (Paffen et al, 2006).…”
mentioning
confidence: 99%